Higher education research in Chile: Publication patterns and emerging themes - Ana Luisa Muñoz-García; Juan Pablo Queupil Quilamán; Andres Bernasconi; Daniela Véliz Calderón (Arizona State University, 2019)
In the context of a recent increase in the Chilean production of knowledge within the field of higher education, this article reveals some trends exhibited by this production, as well as the main research topics. With this aim, we examine the number and institutional affiliations of research grants in the area, provide a bibliometric analysis of Web of Science (WoS) and Scopus publications, and present a content analysis of works indexed in WoS and Scopus published from 2005 to 2015. Results show a clear growth pattern, both in research grants and articles published. Research capacities in the field appear to be distributed across several universities in Chile, and to involve scholars based not only in schools of education, but also those in several other academic units in diverse disciplinary and professional domains. Themes emerging from the content analysis can be grouped in four main research lines: curriculum, teaching and learning; trajectories and experiences of students; the academic profession; and higher education policy.